2010
DOI: 10.1016/j.febslet.2010.07.037
|View full text |Cite
|
Sign up to set email alerts
|

The oocyte‐specific transcription factor, Nobox, regulates the expression of Pad6, a peptidylarginine deiminase in the oocyte

Abstract: a b s t r a c tNobox is an oocyte-specific transcriptional regulator. Nobox deficiency disrupts early folliculogenesis and the expression of oocyte-specific genes in mice. In the present study, we found that peptidylarginine deiminase 6 (Pad6) was downregulated in Nobox-null ovaries. Pad6 is preferentially expressed in oocytes and its transcript is detectable at embryonic day 16.5. In addition, we identified one Nobox DNA-binding element (NBE) within the mouse Pad6 promoter. The NBE includes a core sequence TA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Nobox is an oocyte specific transcriptional regulator and is expressed by germ cell cysts, primordial, and growing follicles . Deficiency of this molecule has been shown to disrupt early folliculogenesis and the expression of several oocyte specific genes in mice . Gap junctions between cumulus and oocyte predominantly contain Gja1 protein.…”
Section: Discussionmentioning
confidence: 99%
“…Nobox is an oocyte specific transcriptional regulator and is expressed by germ cell cysts, primordial, and growing follicles . Deficiency of this molecule has been shown to disrupt early folliculogenesis and the expression of several oocyte specific genes in mice . Gap junctions between cumulus and oocyte predominantly contain Gja1 protein.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst the expression of the Nobox gene has already been described in a number of earlier studies in both mouse (Suzumori et al, 2002;Rajkovic et al, 2004;Choi and Rajkovic, 2006;Choi et al, 2010) and human (Huntriss et al, 2006;Qin et al, 2007), the presence of the NOBOX protein throughout oocyte growth in the adult ovary has never been shown before. The acquisition of this knowledge is central to the understanding of the regulatory role, attributed to the NOBOX protein, upstream of a number of genes crucial to oocyte growth e.g., Oct4, Gdf9, Bmp15, Fgf8, H1oo, Mos, Rfpl4, Zar1 and Dnmt1o (Rajkovic et al, 2004;Choi and Rajkovic, 2006).…”
Section: Discussionmentioning
confidence: 95%
“…Gdf9, Bmp15,Pou5f1,Zar1,Oog1,Pad6,Oosp1,Oct4) are directly or indirectly regulated by NOBOX because KO mice have shown differential expression patterns compared to wild type (WT) animals (Rajkovic et al, 2004). Direct binding to promoter regions has been demonstrated for Gdf9, Pou5f1 and Pad6 (Choi et al, 2010;Choi and Rajkovic, 2006). Very recently, it has been shown that NOBOX and FOXL2 can form a complex to regulate specific target genes in granulosa cells (Bouilly et al, 2014).…”
Section: Noboxmentioning
confidence: 99%